“De la ley a la práctica: la transmisión de los bienes en el seno de la familia Cepeda durante el siglo XVIII (Villalba del Alcor, Huelva)”. - Cristina Ramos Cobano (Nuevo mundo - Mundos Nuevos, 2008)
As a guarantee of social status and prestige, the consolidation of heritage was of paramount importance to the families of the elite, to the point that nearly all transcendent decisions were conditioned by the need to secure it despite partitions and legislation against it. To achieve this, they did not hesitate to take advantage of a wide range of predetermined mechanisms, aiming to prevent excessive partitions, whilst they made efforts for its expansion. Most of these mechanisms were based on exclusion.